The Role of the Village Government in Improving Community Literacy Through the Evening Study Hour (JBM) Program in Sibolangit Village - Artha Eka Putri Ikhwani; Faisal Riza (Journal of Educational Sciences, 2026)
Community literacy remains a challenge in improving the quality of human resources, particularly in rural areas. This study aims to analyze the role of the Sibolangit Village Government in improving community literacy through the Night Study Program (Jam Belajar Malam). A descriptive qualitative approach was employed using observation, documentation, and semi-structured interviews with the village head, village officials, parents, and program participants. Data were analyzed using the Miles and Huberman interactive model. The findings reveal that the village government plays four roles: regulator, facilitator, dynamiter, and catalyst. It initiated and coordinated the program, provided learning facilities, encouraged community participation, and supported its sustainability. The program has improved children's learning discipline, reading motivation, and study habits while reducing excessive mobile phone use during the evening. However, its implementation is constrained by limited funding, inadequate facilities, declining participation among junior high school students, and inconsistent parental support. Overall, the Night Study Program has become an effective community-based non-formal education initiative that contributes to strengthening the learning culture and improving literacy in Sibolangit Village.